Farmer responses to technical advice offered at plant clinics in Malawi, Costa Rica and Nepal - Bentley, Jeffery W.; Danielsen, Solveig; Phiri, Noah; Tegha, Yakosa C.; Nyalugwe, Nixon; Neves, Eduardo [UNESP]; Hidalgo, Eduardo; Sharma, Abhishek; Pandit, Vinod; Sharma, Dilli Ram (Taylor & Francis, 2018)
This study explores how communication and its technical content shape farmers’ response to advice delivered at plant clinics. Thirty-six farmers who visited a plant clinic in one of three countries (Malawi, Costa Rica and Nepal) were given at least one diagnosis of a plant health problem and up to six options for managing the problem. Almost all of the farmers were able to use at least some of these management recommendations. Communication was verbal, but reinforced in writing; all of the farmers received a one-page prescription form that summarized the recommendation. Communication per se was rarely the reason farmers failed to adopt technologies. Farmers who opted not to use recommendations often had logical, material reasons for doing so, and they showed a preference for chemical control. Of the 31 farmers who were advised to apply pesticides (including organic ones), 23 people (74%) accepted this advice to spray, but only 14 of 22 farmers (54%) tried advice for cultural or biological control. Farmers’ response to an innovation is too complex to always describe as accepted vs rejected, and this decision depends on the fit of the technology itself, and on the quality of how the innovation is communicated.
Keywords: adoption of technology; agricultural extension; communication; Plant clinics